Influences Of Sales Growth And Leverage On Profitability (Empirical Study of Manufacturing Companies in the Consumer Goods Sector listed on the Indonesia Stock Exchange for the 2016-2019 Period) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the relationship between the effect of sales growth and leverage on profitability. The factors tested in this study are sales growth and leverage as independent variables. Meanwhile, profitability is the dependent variable. The research method used in this research is descriptive and verification research methods. The population in this study were 53 companies in the consumer goods sector. The data collection technique used in this study is to use financial reports with a total sample of 27 companies in the consumer goods sector. While the analysis method used in this research is panel data regression analysis at a significance level of 5%. The program used in analyzing the data used Eviews 10. The results showed that sales growth had a significant positive effect on profitability, while leverage had no effect on profitability.